© h.hofstede (h.hofstede@hogeland.nl)

       
1. a. cosx • dy/dx = cos2x - sinx • y  
dy/dx = cosx - sinx/cosx • y
dy/dx + sinx/cosx • y = cosx
f
  =  sinx/cosx = tanx dus   f = -ln(cosx)
h = e
f  = e-ln(cosx) = (cosx)-1
hg = (cosx)-1 • cosx = 1   dus   ∫ hg = x
y(c + x)/(cosx)-1  =  c • cosx + xcosx  
       
  b. xy'  = 2y + 3x4 + 2
y ' = 2y/x + 3x3 + 2/x
y
' - y • 2/x = 3x3 + 2/x
f
  =  -2/x  dus  f  = -2lnx
h
= e ∫ f
  = e-2lnx  = x-2
hg = x-2 • (3x3 + 2/x) = 3x + 2x-3   dus  hg  = 11/2x2 - x-2
y = (c + 1,5x2 - x-2)/x-2  = cx2 + 11/2x4 - 1
       
  c. dy/dx + 2xy = 2x
f
= 2x  dus  f  = x2
h = ef  = ex² 
hg = 2xex²   dus  ∫ hg = ex² 
y = (c + ex²) / ex
²ce-x² + 1
       
  d. 2 dy/dx + y = 2xx
dy/dx1/2x • y  = √x
f
  = 1/2x = 1/2 • 1/x dus   f  =  1/2lnx  
h =  e
f  =  e0,5lnx = x
hg
=
x • x = dus  ∫ hg = 1/2x2
y =
(c + 0,5x²)/
x  = c/x + 1/2xx
       
  e. y' - 2y =  e3x
f  = 
-2  dus  f = -2x
h
= ef = e-2x
hg  = e-2x • e3x = ex   dus  ∫ hg = ex
y = (c + ex) / e-2x  =  c
• e2x + e3x  
       
  f. x2 y'  + xy = x2 + 1
y ' + y/x  = 1 + 1/x²
f
= 1/x  dus  f = lnx
h
= e f  = elnx  = x
hg
= x + 1/x   dus  hg = 1/2x2 + lnx
y
= (c +  0,5x2 + lnx)/ x  = c/x + 1/2x + lnx/x
       
  g. y' + y/(x - 1) = 1/(x - 1)(x + 3) 
f1/(x- 1)  dus  f = ln(x - 1)
h = ef   = eln(x
- 1) = x - 1
hg = 1/(x + 3)  dus  hg  = ln(x + 3)
y(c + ln(x + 3))/(x - 1)   
       
  h. (1 + x2) • y'  + 2xy = 1 + x2   
y' + 2x/(1 + x²) • y = 1
f = 2x/(1 + x²)  dus  f = ln(1 + x2)
h = efeln(1 + x²) = 1 + x2
hg = 1 + x2  dus  ∫ hg = x + 1/3x3
y =  (c + x + 1/3x3 )/(1 + x2)
       
  i. y' x - 3y = 7x
y ' -
3/x • y =  7
f =  -3/x  dus  f  = -3lnx
h
= efe-3lnx  = x-3
hg = x-3 • 7  dus  ∫ hg = -7/2x -2 
y = (c - 7/2x-2) / x-3  =  cx3 - 7/2x
       
  j. y'  + 3y = e-3x
f =
  3 dus  f  = 3x
h
= ef = e3x
hg = e3x • e-3x = 1  dus  ∫ hg = x
y
= (c + x)/e3x  = (c + x) • e-3x
       
  k. xy' + 2y = 8x2
y ' + 2/x • y = 8x
f
= 2/x  dus  f = 2lnx
h
= e f = e2lnx = x2
hg = x2 • 8x = 8x3  dus ∫ hg = 2x4
y = (c + 2x4) / x2  =  cx -2 + 2x2
 
       
  l. xy'  - 4y = x6ex
y '  -
4/x • y = x5ex
f
= -4/x  dus  f = -4lnx
h
= e∫ f  = e-4lnx  = x-4
hg = x-4 • x5ex  =  xex   dus  ∫ hg =
xex - ex
y
= (c + xex - ex) / x-4  =  cx4 + x5ex - x4ex
       
  m. cosx • y'  + ysinx = 2cos3xsinx - 1
dy/dx + y sinx/cosx  = 2cos2xsinx - 1/cosx
f
  = sinx/cosx = tanx  dus  f = -ln(cosx)
h = ef  = e-ln(cosx) =  (cosx)-1 
hg = 2cosxsinx1/cos²x  = sin2x - 1/cos²x
hg  = -1/2cos2x - tanx
y =
(c - 1/2cos2x - tanx) • cosx
y
= c • cosx - 1/2cos2xcosx - tanxcosx  
       

© h.hofstede (h.hofstede@hogeland.nl)